Peningkatan Pemahaman Konsep Matematika dengan Menggunakan Model Realistic Mathematics Education di SDN Binangun - Priyanti Sularso, Bekti Ayu; Supriyono, Supriyono; Khaq, Muflikhul (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2021)
This study aims to determine the increase in understanding of mathematical concepts using the Realistic Mathematics Education model in fourth-grade students at SD Negeri Binangun. The subjects in this study were fourth-grade students at SD Negeri Binangun, Need District, Purworejo Regency, totalling 21 students consisting of 14 boys and seven girls, in the 2020/2021 school year. This study used Classroom Action Research (CAR) which was conducted in two cycles, each cycle having two meetings. Data collection techniques using test instruments, observation and documentation. Data analysis was carried out with qualitative and quantitative methods. The results showed that the understanding of students' concepts had increased. This is shown in the first cycle the average value has increased by 18.7%, with an average value of 75.7. In the second cycle, the average value has increased again by 12.1%, with an average value of 87 students' conceptual understanding. 8. Thus, it can be conclude that the Realistic Mathematics Education learning model can improve knowledge of mathematical concepts in fourth-grade students at SD Negeri Binangun